THE EFFECTIVENESS OF TPR (TOTAL PHYSICAL RESPONSE) METHOD IN IMPROVING ENGLISH VOCABULARY MASTERY OF ELEMENTARY SCHOOL CHILDREN - Sariyati, Ice (2013)
This research employed an embedded mixed method, combining quantitative and qualitative methods. To achieve the aims of the study, a quasi-experimental design was used, involving two groups (control and experiment) at the first grade in one Islamic elementary school in Bandung and employing pretest, treatment (TPR method to experiment group, conventional method to control group) and posttest. Besides, observation by field notes was employed to know the students' response to TPR method. The findings of data analysis revealed that the result of control class score computation to compare pretest score with posttest score showed that the significance is 0.117 which is > 0.05 (level of significance). Since it is higher than 0.05, the null hypothesis is accepted. It means that there is no significant difference between the pre-test and post-test score of control class. On contrary, the result of experiment class score computation to compare pretest score with posttest score showed that the significance is 0.000 which is < 0.05. Since it is lower than 0.05 (level of significance), the null hypothesis is rejected. It means that there was significant difference between the pretest and posttest score of experiment class. Therefore, it can be concluded that the vocabulary mastery of experiment group was significantly improved. In addition, the data from observation using field note showed that generally, the students had good response toward TPR method used in the learning activity. It was indicated by during this learning process, the students looked enthusiastic, participated well and happily without any stress condition. Besides, they understood both the classroom language and the learning material. Hence, it can be inferred that the Total Physical Response method is effective and suitable to be used for elementary school children to learn English, especially English vocabulary as it makes them learn it more easily and happily.